2012
DOI: 10.4081/ams.2012.e3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin in transgenic Drosophila melanogaster model of Parkinson’s disease

Abstract: Studies on model organisms have been found to be invaluable in clarifying the cellular and molecular basis of normal cellular processes and disease pathogenesis. Drosophila mutants and transgenes have provided a platform to understand the mechanisms associated with degenerative disease. Studies on the role of polyphenols in protecting against neurodegenerative diseases are limited. In the present study, the effect of curcumin at various doses was studied on the climbing ability of the transgenic Drosophila mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…The efficacy of levodopa declines as PD progresses, but the oxidative stress can be reduced by agents having the free radical scavenging potential [50]. Our earlier studies with nordihydroguaiaretic acid [51], curcumin [52], capsaicin [53], and ascorbic acid [54] also showed a dose-dependent delay in the loss of climbing ability in the same PD model flies. The study with ascorbic acid, a well known antioxidant that showed no significant difference in the protein levels in the brain of PD model fly, suggests that only free radical scavenging activity is involved in the protection against the PD symptoms [54].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of levodopa declines as PD progresses, but the oxidative stress can be reduced by agents having the free radical scavenging potential [50]. Our earlier studies with nordihydroguaiaretic acid [51], curcumin [52], capsaicin [53], and ascorbic acid [54] also showed a dose-dependent delay in the loss of climbing ability in the same PD model flies. The study with ascorbic acid, a well known antioxidant that showed no significant difference in the protein levels in the brain of PD model fly, suggests that only free radical scavenging activity is involved in the protection against the PD symptoms [54].…”
Section: Discussionmentioning
confidence: 99%
“…Crosses were set up as described in earlier published work [12]. The PD flies were exposed separately to different doses of curcumin (Sigma Aldrich, CAS 458-37-7) and mixed in culture medium at final concentration of 25, 50, and 100  μ M. The PD flies were also exposed to 10 −3  M of L-dopamine.…”
Section: Methodsmentioning
confidence: 99%
“…The flies were cultured on standard Drosophila food containing agar, corn meal, sugar, and yeast at 25°C (24 ± 1) [ 10 ]. Crosses were set up as described in our earlier published work [ 11 ]. First, the climbing assay was performed for the PD flies and UAS-Hsap/SNCA.F (control).…”
Section: Methodsmentioning
confidence: 99%